The first red list of Italian butterflies. Issue 5 (26th February 2018) - Bonelli, Simona; Casacci, Luca P.; Barbero, Francesca; Cerrato, Cristiana; Dapporto, Leonardo; Sbordoni, Valerio; Scalercio, Stefano; Zilli, Alberto; Battistoni, Alessia; Teofili, Corrado; Rondinini, Carlo; Balletto, Emilio
Abstract: The Italian biodiversity is among the richest in Europe. In particular, the Italian butterfly fauna includes almost 300 native species, and within the Euro‐Mediterranean area is second in species richness only to Turkey. Italy, however, has suffered from the lack of suitable instruments to evaluate the extinction risk of individual butterfly species on the basis of internationally recognised standards. We have been working to create the first Italian Red List for butterflies. The achievement of this goal was divided into three actions: (i) the institution of a network of experts on butterfly conservation; (ii) the evaluation of the extinction risk for all Italian butterfly species; (iii) the integration of the baseline information provided by the Italian Red Lists of other taxa crucial for future evaluations of biodiversity trends in Italy. Assessments of extinction risks were based on the IUCN Red List Categories and Criteria following their most updated guidelines and were discussed during workshops involving experts from different Italian regions. All native Italian butterflies were included in the evaluation. The whole national population of each species was evaluated, including those on large and small islands. Of 289 butterfly species assessed, one has become Regionally Extinct recently. Threatened species are 18 in total, corresponding to 6.3% of the species assessed. The majority of Italian butterfly populations are stable. The main threats to Italian butterflies are natural reforestation, as a consequence of rural land abandonment, agricultural intensification and climate change for species living at high altitude.